2009
DOI: 10.1007/s11581-009-0338-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of polypyrrole–indium phosphide composite film

Abstract: Polypyrrole (PPy)-indium phosphide (InP) composite material was electrochemically prepared by the incorporation of InP into a PPy matrix during electrochemical synthesis (cycling) under magnetic stirring from the acetonitrile/LiClO4 electrolyte containing the Py and InP particles. The PPy-InP composite material was designed to explore new approaches to improve light-collection efficiency in polymer photovoltaic. The samples were characterised by cyclic voltammetry, impedance spectroscopy measurement, scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…This results matches with the earlier reported data [12], that the bands at nearly 421 nm resulting from the π to π* transition. And the large shoulder beyond the 800 nm , indicating that the conducting polymer is in oxidizes and conducting state [12,13].…”
Section: B Optical Absorption Studysupporting
confidence: 94%
See 1 more Smart Citation
“…This results matches with the earlier reported data [12], that the bands at nearly 421 nm resulting from the π to π* transition. And the large shoulder beyond the 800 nm , indicating that the conducting polymer is in oxidizes and conducting state [12,13].…”
Section: B Optical Absorption Studysupporting
confidence: 94%
“…And the large shoulder beyond the 800 nm , indicating that the conducting polymer is in oxidizes and conducting state [12,13].…”
Section: B Optical Absorption Studymentioning
confidence: 99%
“…However, in the case of the insoluble polymers, the dispersion of the nanoparticles is carried out by stirring during electropolymerization. We note that the previous similar studies [31][32][33] have shown that TiO 2 incorporation into PPy films during electrochemical synthesis under magnetic stirring in order to improve the composite performance to anticorrosion [34].…”
Section: Introductionmentioning
confidence: 56%
“…Frank and Honda [10] observed that CdS covered with PPy and activated with the RuO 2 under anodic potentials of 0.4 V (vs. SCE) in 0.5 M Na 2 SO 4 increases the rate of the oxygen production from 1% for pure CdS, to 21% for PPy covered, and up to 68% for RuO 2 activated. Recently, different authors investigated the influence of the PPy on the photoelectrochemical behavior of some semiconductors, CdS [11], InP [12], Bi 2 S 3 [13,14] and GaAs [15]. In all the investigations, the PPy-semiconductor was prepared as a composite film, with semiconductor particles incorporated under mixing conditions, during pyrrole electropolymerization.…”
Section: Introductionmentioning
confidence: 99%